Journey to Smart City: The Case of Smart City Development in Karanganyar Regency - Muhammad Nurul Huda; Muhammad Samsuri; Rauhulloh Ayatulloh Khomeini Noor Bintang (Kybernology : Journal of Government Studies, 2023)
A smart city is a modern and advanced city that is integrated with digital systems that support convenience and comfort for its residents. Initially, the smart city concept was aimed at developed countries that have adequate infrastructure, but in Indonesia, district or city governments can improvise in its implementation according to the needs and capabilities of local governments. The aim of this research is to analyze the obstacles and strategies for implementing smart cities that are adapted based on the conditions of the Karanganyar Regency area. The research method uses descriptive-qualitative research, which is linked to empirical reality with applicable theory. Data is obtained from journal references, regional regulations, the Karanganyar Regency smart city master plan book, etc. The results show that the journey towards a smart city in Karanganyar Regency has been documented in the 2018–2023 RPJMD, but its implementation is faced with infrastructure (technology), structural (HR and budget), and superstructure (institution and policy) problems.